Inter-hospital COVID ECMO air transportation. (May 2021) - Salas de Armas, Ismael A; Akkanti, Bindu H; Janowiak, Lisa; Banjac, Igor; Dinh, Kha; Hussain, Rahat; Cabrera, Rodolfo; Herrera, Tony; Sanger, Damon; Akay, Mehmet H; Patel, Jayeshkumar; Patel, Manish K; et al.
The Coronavirus Disease 2019 (COVID-19) pandemic has required rapid and effective protocol adjustments at every level of healthcare. The use of extracorporeal membrane oxygenation (ECMO) is pivotal to COVID-19 treatment in cases of refractory hypoxemic hypercapnic respiratory failure. As such, our large, metropolitan air ambulance system in conjunction with our experts in advanced cardiopulmonary therapies modified protocols to assist peripheral hospitals in evaluation, cannulation and initiation of ECMO for rescue and air transportation of patients with COVID-19 to our quaternary center. The detailed protocol is described alongside initial data of its use. To date, 14 patients have been placed on ECMO support at an outside facility and successfully transported via helicopter to our hub hospital using this protocol.